Trace and ultratrace metals in bottled waters: survey of sources worldwide and comparison with refillable metal bottles - Krachler, Michael; Shotyk, William (The science of the total environment, 2009)
Bottled waters from diverse natural and industrial sources are becoming increasingly popular worldwide. Several potentially harmful trace metals (Ag, Be, Li, Ge, Sb, Sc, Te, Th, U) are not monitored regularly in such waters. As a consequence, there is extremely limited data on the abundance and potential health impacts of many potentially toxic trace elements. Containers used for the storage of bottled waters might also increase trace metal levels above threshold limits established for human consumption by the EPA or WHO. Applying strict clean room techniques and sector field ICP-MS, 23 elements were determined in 132 brands of bottled water from 28 countries. In addition, leaching experiments with high purity water and various popular metal bottles investigated the release of trace metals from these containers. The threshold limits for elements such as Al, Be, Mn and U in drinking water were clearly exceeded in some waters. Several bottled waters had Li concentrations in the low mg/L range, a level which is comparable to blood plasma levels of patients treated against manic depression with Li-containing drugs. The rate of release of trace metals from metal bottles assessed after 13 days was generally low, with one exception: Substantial amounts of both Sb and Tl were released from a commercially available pewter pocket flask, exceeding international guidelines 5- and 11-fold, respectively. Trace metal levels of most bottled waters are below guideline levels currently considered harmful for human health. The few exceptions that exist, however, clearly reveal that health concerns are likely to manifest through prolonged use of such waters. The investigated coated aluminium and stainless steel bottles are harmless with respect to leaching of trace metals into drinking water. Pocket flasks, in turn, should be selected with great care to avoid contamination of beverages with harmful amounts of potentially toxic trace metals such as Sb and Tl.
Available online 6 November 2008
Gesehen am 28.09.2020